Relationship of urban heat with building density and green spaces - a remote sensing-based study across Vietnam’s metropolitan areas - Braun, Andreas; Duffy, Carolyn Elizabeth; Warth, Gebhard; Hochschild, Volker (Vietnam Journal of Science and Technology, 2023)
Urban heat island effects are an increasing challenge for metropolitan areas, especially in regions where climate change increases the frequency of extreme temperatures. The consequences for human health are understood and must be addressed by urban planning. Although many studies currently exist regarding relationships of adaptation measures and urban heat amongst individual single cities, there is little general understanding on how urban development impacts temperature at large scales. In this study we analyze the correlation between urban heat and two indicators of urban morphology: the green spaces and the density of buildings. We hypothesize that the relation between building density, urban green space and urban surface temperature can be quantified openly available techniques of Earth observation. To grant an objective and consistent analysis over the entire country of Vietnam, we use information from different high-resolution imaging satellites. The computation of Pearson correlations across 58 Vietnamese districts confirms the hypothesis, indicating a negative impact of urban green space (-0.217), a positive impact of building density (+0.392) and an even stronger relationship with both indicators combined (+0.435). The findings are discussed with data of three research projects involving the cities of Hồ Chí Minh, Đà Nẵng, and Huế, and interpreted regarding regional differences and implications for urban planning.